2011
DOI: 10.1177/1010539511402191
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Liver and Metabolic Syndrome in Nonabdominally Obese Taiwanese Adults

Abstract: The aim of this study was to examine the relationship between fatty liver (FL), abdominal obesity, and metabolic syndrome (MetS). A total of 3058 adults who underwent health examinations in 2005 were enrolled. MetS was defined according to the National Cholesterol Educational Program's Adult Treatment Panel III criteria. The relationship between FL, abdominal obesity, and MetS was analyzed using multiple logistic regression. The authors found that participants with FL alone [FL(+)/abdominal obesity(-)] had a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
0
8
1
Order By: Relevance
“…It has been demonstrated by several studies that higher risk of metabolic disorders is found in patients with NAFLD than in those without it. 15 , 16 However, since data on metabolic disorders and NAFLD were collected and analyzed cross-sectionally, the causal association between metabolic disorders and NAFLD is unclear. Moreover, although there was a significant association between diabetes and NAFLD, 17 neither a history of diabetes nor high FBG served as an independent risk factor for NAFLD on multivariate analyses suggesting that diabetes is a confounding factor.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated by several studies that higher risk of metabolic disorders is found in patients with NAFLD than in those without it. 15 , 16 However, since data on metabolic disorders and NAFLD were collected and analyzed cross-sectionally, the causal association between metabolic disorders and NAFLD is unclear. Moreover, although there was a significant association between diabetes and NAFLD, 17 neither a history of diabetes nor high FBG served as an independent risk factor for NAFLD on multivariate analyses suggesting that diabetes is a confounding factor.…”
Section: Discussionmentioning
confidence: 99%
“…Increased fat accumulation in the liver may suppress hepatic insulin clearance and lead to hyperinsulinemia or hyperglycemia (30); this effect is independent of obesity (31). Several earlier studies demonstrated a higher risk of metabolic disorders in patients with NAFLD than in those without (17,21). However, since data on metabolic disorders and NAFLD were collected and analyzed cross-sectionally, the causal association between metabolic disorders and NAFLD is unclear.…”
Section: Discussionmentioning
confidence: 94%
“…Although a large body of evidence was identified in the literature regarding the cross-sectional association between metabolic disorders and NAFLD (15,1722,28), the longitudinal effect of MS on the development of NAFLD was unclear. An earlier survey in Shanghai, China including 3,175 middle-aged adults, identified that participants with metabolic disorders, including central obesity, diabetes, dyslipidemia or hypertension, increased the risk of fatty liver by 33-, 32-, 23- or 23-fold, respectively (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies even demonstrated that the quantity of liver fat was more closely linked to the metabolic complications of obesity than that of visceral fat. Chang and Chen displayed subjects with only NAFLD had a greater odds ratio for developing abnormal MetS components than those with only abnormal WC [ 20 ]. Stefan et al reported that liver fat had stronger correlation with insulin sensitivity than visceral adipose tissue among the obese subjects [ 19 ].…”
Section: Discussionmentioning
confidence: 99%